1996
DOI: 10.2527/1996.7492067x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the level of asphyxia during delivery on viability at birth and early postnatal vitality of newborn pigs.

Abstract: Newborn pigs (n = 117) were used to provide information on the relationships of degree of asphyxia during delivery, viability at birth, and some striking aspects of postnatal vitality including survival, interval between birth and first udder contact and between birth and first suckling, rectal temperature at 24 h of life (RT24), and growth rate over the first 10 d of life. The degree of asphyxia at birth was estimated from cord blood pCO2, pH, and lactate levels. Onset of respiration, heart rate, skin color, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
193
7
13

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(250 citation statements)
references
References 16 publications
24
193
7
13
Order By: Relevance
“…After birth, those weak piglets which died before weaning consumed less colostrum and therefore lost weight as also observed in other studies (Thompson and Fraser, 1988;de Passillé and Rushen, 1989). The same piglets also exhibited hypoglycemia, high cortisol concentration and lower IgG intake, which often characterize piglets that die before weaning as already demonstrated (Tyler et al, 1990;Herpin et al, 1996;Tuchscherer et al, 2000). Therefore, the present findings support previous observations that weak piglets, whatever the cause of their weakness (low birth weight, hypoxia or malformation), are disadvantaged for colostrum intake (Devillers et al, 2007) and enter a vicious cycle where low colostrum intake leads to hypoglycemia and hypothermia (Herpin et al, 2002) and beyond to high plasma cortisol and lactate concentrations, which are characteristic of glycogen reserve mobilization and high gluconeogenesis (Lepine et al, 1989).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…After birth, those weak piglets which died before weaning consumed less colostrum and therefore lost weight as also observed in other studies (Thompson and Fraser, 1988;de Passillé and Rushen, 1989). The same piglets also exhibited hypoglycemia, high cortisol concentration and lower IgG intake, which often characterize piglets that die before weaning as already demonstrated (Tyler et al, 1990;Herpin et al, 1996;Tuchscherer et al, 2000). Therefore, the present findings support previous observations that weak piglets, whatever the cause of their weakness (low birth weight, hypoxia or malformation), are disadvantaged for colostrum intake (Devillers et al, 2007) and enter a vicious cycle where low colostrum intake leads to hypoglycemia and hypothermia (Herpin et al, 2002) and beyond to high plasma cortisol and lactate concentrations, which are characteristic of glycogen reserve mobilization and high gluconeogenesis (Lepine et al, 1989).…”
Section: Discussionsupporting
confidence: 76%
“…The amount of colostrum ingested is highly variable between piglets and depends on both the sow's ability to produce enough colostrum for the whole litter and the piglet's ability to extract colostrum from the teats. Since colostrum production is independent of litter size (Devillers et al, 2007), factors influencing a piglet's colostrum intake, such as low birth weight and vitality (Herpin et al, 1996;Tuchscherer et al, 2000;Devillers et al, 2007), are crucial for its survival. Most of the studies looking at the role of the colostrum in piglet physiology and immunity were conducted in experimentally controlled conditions using force-or bottle-feeding.…”
Section: Introductionmentioning
confidence: 99%
“…At birth, piglets were weighed and time of day was recorded. Because of their link to hypoxia during delivery (Herpin et al, 1996), some birth characteristics were also recorded to assess vitality (umbilical cord already ruptured, difficulty to breathe (more than 5 s until first attempt to breathe), piglet still inside placental membranes). Piglets born in placental membranes were extirpated from them and reanimated, if necessary.…”
Section: Animals and Measurementsmentioning
confidence: 99%
“…Colostrum intake by piglets depends not only on their ability to extract colostrum from teats but also on the ability of sows to produce enough colostrum for the whole litter (Hoy et al, 1997). Indeed, negative effects of low birth weight and poor vitality (asphyxia during delivery, long time from birth to first suckling) on colostrum intake were demonstrated in several studies (Herpin et al, 1996;Tuchscherer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It may be due to a higher risk of hypoxia resulting from uterine contractions that reduce oxygenation of the unborn piglets, early placenta detachments, or damage or premature ruptures of the umbilical cords. Such disturbances are more frequent in large litters (Herpin et al, 1996;Alonso-Spilsbury et al, 2005). Several studies have demonstrated the important association between farrowing kinetics (duration and rhythm) and stillbirth (e.g.…”
Section: Introductionmentioning
confidence: 99%